2008
DOI: 10.1139/x07-173
|View full text |Cite
|
Sign up to set email alerts
|

Silvicultural responses of two spruce plantations to midrotation commercial thinning in New Brunswick

Abstract: A midrotation commercial thinning experiment conducted in two independent spruce plantations compared several tree selection strategies as both early (age 19 or 24 years) single and double (again at age 30 or 34 years) entries over a 16 year period. A delayed (age 30 or 32 years) single-entry thinning and unthinned portions of the plantations served as references for the other treatments. With the exception of 50% systematic row thinnings, removal intensities were held relatively constant at about 40% of stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 11 publications
1
32
0
1
Order By: Relevance
“…CT of plantations occurs when size of thinned trees permits conversion to useable wood products to increase commercial productivity (Nyland 2002, Pelletier andPitt 2008). To contribute to biodiversity conservation while procuring renewable timber (Vincent et al 2009), traditional silvicultural practices which focus primarily on wood production may need to be modified.…”
Section: Introductionmentioning
confidence: 99%
“…CT of plantations occurs when size of thinned trees permits conversion to useable wood products to increase commercial productivity (Nyland 2002, Pelletier andPitt 2008). To contribute to biodiversity conservation while procuring renewable timber (Vincent et al 2009), traditional silvicultural practices which focus primarily on wood production may need to be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Clune (2013) studied spruce-fir response to a combination of commercial thinning methods, timings and intensities of removal over the past decade in Maine, with results showing the benefit of CT on stand stability and growth. CT has been shown to focus diameter and volume growth on a selected number of stems and therefore decreases the growing time to a specific merchantable volume (Pelletier and Pitt 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to the result of Emmingham et al [49] who found that low-thinned and crown-thinned stands grew up to 124% more volume than the control. In New Brunswick, Canada, a study by Pelletier and Pitt [50] showed that all of the tested CT treatments resulted in improved diameter and volume growth on fewer individual trees. They further reported that early thinning entries increased the merchantable volume per stem by up to 24% over unthinned controls.…”
Section: Thinning Effect On Average Merchantable Stem Sizementioning
confidence: 99%